The effect of semi-pelagic trawling on american plaice (hippoglossoides platessoides) by-catch reduction in the northeast arctic shrimp fishery - Sistiaga, Manu Berrondo; Grimaldo, Eduardo; Herrmann, Bent; Larsen, Roger B. (Memorial University of Newfoundland, Fisheries and Marine Institute, Centre for Applied Ocean Technology, 2017)
Source at http://www.thejot.net/?page_id=837&show_article_preview=867 The present study reports results of a small-scale preliminary experiment to evaluate whether lifting trawl doors and sweeps from the seabed can lead to a reduction of by-catch in the Northeast Arctic shrimp trawl fishery. We carried out a catch comparison and catch ratio analysis between two gear configurations: one with trawl doors and sweeps on the seabed (traditional rigging) and the other with doors and sweeps clear of the seabed (semi-pelagic rigging). The study focused on the by-catch of American plaice (Hippoglossoides platessoides) and showed that the gear was significantly less efficient at catching this species when rigged in the semi-pelagic mode. When rigged this way, the gear captured 52%–66% fewer American plaice between 10 and 40 cm compared to traditional rigging. Moreover, this difference was significant for sizes between 12 and 31 cm, and it increased with fish size. The herding efficiency of doors and sweeps for American plaice was estimated to be 100% and significantly higher than 0 for these sizes. Finally, the analysis carried out did not detect a significant reduction in shrimp catch (in kg) with the experimental gear. This study demonstrates that in addition to having recognized environmental advantages, lifting the doors and sweeps from the seabed could help mitigate American plaice by-catch in the Northeast Arctic shrimp fishery. Although these preliminary results are promising, more extensive data collection is required before definitive conclusions can be reached.